2014
DOI: 10.4056/sigs.5661021
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the Radiation-Resistant bacterium Rubrobacter radiotolerans RSPS-4

Abstract: Rubrobacter radiotolerans strain RSPS-4 is a slightly thermophilic member of the phylum “Actinobacteria” isolated from a hot spring in São Pedro do Sul, Portugal. This aerobic and halotolerant bacterium is also extremely resistant to gamma and UV radiation, which are the main reasons for the interest in sequencing its genome. Here, we present the complete genome sequence of strain RSPS-4 as well as its assembly and annotation. We also compare the gene sequence of this organism with that of the type strain of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 83 publications
0
45
0
Order By: Relevance
“…No PTS‐type transporters were identified in G. occulta genome. By in large, S. soli and R. radiotolerans have similar ABC transporters for sugars (Egas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No PTS‐type transporters were identified in G. occulta genome. By in large, S. soli and R. radiotolerans have similar ABC transporters for sugars (Egas et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes coding for enzymes involved in the synthesis of mannosylglycerate or di‐ myo ‐inositol‐phosphate were not identified in G. occulta . In R. radiotolerans , trehalose synthesis can proceed via four pathways namely TpS/TpP, TreS, TreT, and TreY/TreZ (Egas et al, ; Nobre et al, ). In G. occulta only the genes coding for TpS/TpP and TreS were detected in the genome ( tpS , EC 2.4.1.15, Gocc_2203, tpP , EC 3.1.3.12, Gocc_2154, treS , EC 5.4.99.16, Gocc_0097).…”
Section: Resultsmentioning
confidence: 99%
“…Results presented here show that homologs showing high degree of sequence similarity to the BchB and BchN proteins are present in two sequenced Rubrobacter species (R. xylanophilus and R. radiotolerans), belonging to the phylum Actinobacteria (family Rubrobaceteraceae, order Rubrobacterales) (Yarza et al 2008;Gao and Gupta 2012;Egas et al 2014;Albuquerque et al 2014). The phylum Actinobacteria is composed of high G?C Grampositive bacteria (Goodfellow et al 2011;Gao and Gupta 2012), and there is no prior indication of the presence of photosynthesis, or any evidence pertaining to it, in the members of this phylum.…”
Section: Discussionmentioning
confidence: 89%
“…These studies revealed that in BLASTp searches with the BchB and BchN proteins, in addition to the expected presence of homologs of these proteins in different photosynthetic organisms (Beale 1999;Raymond et al 2002;Mulkidjanian et al 2006;Gupta 2012), homologs exhibiting low expect values (E values), in the range of 2e -32 to 5e -53 , were also present in the two genome sequenced species from the genus Rubrobacter (viz. R. xylanophilus and R. radiotolerans) ( Table 1) (Egas et al 2014). The BchL, BchN, and BchB proteins are also known to exhibit sequence/structural similarity to the three subunits of chlorin reductase (viz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation